2011
DOI: 10.1073/pnas.1100307108
|View full text |Cite
|
Sign up to set email alerts
|

Endemic social diversity within natural kin groups of a cooperative bacterium

Abstract: The spatial structure of genetic diversity underlying social variation is a critical determinant of how cooperation and conflict evolve. Here we investigated whether natural social groups of the cooperative soil bacterium Myxococcus xanthus harbor internal genetic and phenotypic variation and thus the potential for social conflict between interacting cells. Ten M. xanthus fruiting bodies isolated from soil were surveyed for variation in multiple social phenotypes and genetic loci, and patterns of diversity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(117 citation statements)
references
References 73 publications
3
114
0
Order By: Relevance
“…Colonymerger incompatibilities evolve readily in both natural populations [16] and experimental lineages (P. Zee & O. Rendueles-Garcia 2012, unpublished results) and might be selectively favoured in soil habitats due to the barriers to inter-migration among non-kin from divergent groups that they create [52]. The potential for chimaeric load to result from the merging of distinct swarms composed of functionally divergent genotypes would contribute to benefits of colonymerger incompatibilities and favour their reinforcement.…”
Section: (B) Evolutionary Originsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colonymerger incompatibilities evolve readily in both natural populations [16] and experimental lineages (P. Zee & O. Rendueles-Garcia 2012, unpublished results) and might be selectively favoured in soil habitats due to the barriers to inter-migration among non-kin from divergent groups that they create [52]. The potential for chimaeric load to result from the merging of distinct swarms composed of functionally divergent genotypes would contribute to benefits of colonymerger incompatibilities and favour their reinforcement.…”
Section: (B) Evolutionary Originsmentioning
confidence: 99%
“…The potential for chimaeric load to result from the merging of distinct swarms composed of functionally divergent genotypes would contribute to benefits of colonymerger incompatibilities and favour their reinforcement. Such incompatibilities appear to generate a very fine scale of social isolation in natural populations that may lead to longterm divergence among sympatric patches of lineage clusters [16]. In turn, such divergence may increase latent chimaeric load (i.e.…”
Section: (B) Evolutionary Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural diversity in the degree to which cooperative traits are expressed by distinct strains within a common social group has been found or postulated to exist in several microbial species [14][15][16][17]. Examples include variation in quorum-sensing signal production in Pseudomonas aeruginosa [18], bioluminescence in Vibrio fisheri [19], and social swarming [20] and spore production [21] in Myxococcus xanthus.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally variable traits include developmental competitiveness in mixed groups [11,27,42], social swarming rates [20], rate of development [21], allee effects during development [43] and predation range [40]. Kraemer & Velicer [14] found that even closely related clones isolated from within a single fruiting body often vary markedly in their expression of social phenotypes. Three of 10 fruiting bodies they examined harboured genotypes that swarm significantly slower in pure culture than do other clones from the same fruiting body.…”
Section: Introductionmentioning
confidence: 99%